2019
DOI: 10.1021/acs.jpcb.9b07228
|View full text |Cite
|
Sign up to set email alerts
|

Detecting and Characterizing the Kinetic Activation of Thermal Networks in Proteins: Thermal Transfer from a Distal, Solvent-Exposed Loop to the Active Site in Soybean Lipoxygenase

Abstract: The rate-limiting chemical reaction catalyzed by soybean lipoxygenase (SLO) involves quantum mechanical tunneling of a hydrogen atom from substrate to its active site ferric-hydroxide cofactor. SLO has emerged as a prototypical system for linking the thermal activation of a protein scaffold to the efficiency of active site chemistry. Significantly, hydrogen–deuterium exchange-mass spectrometry (HDX-MS) experiments on wild type and mutant forms of SLO have uncovered trends in the enthalpic barriers for HDX with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(55 citation statements)
references
References 69 publications
1
54
0
Order By: Relevance
“…3.1 Å, consistent with the expectation of van der Waals contacts [21]. The reduction in this distance thus occurs transiently and may be facilitated by defined protein conformational networks involved in thermal activation [27,94]. The efficiency of active site compaction is influenced by proper steric bulk of hydrophobic residues at the active site [26,43,95,96].…”
Section: Second-order Kies Indicate Substrate Binding As Partial Ratesupporting
confidence: 79%
“…3.1 Å, consistent with the expectation of van der Waals contacts [21]. The reduction in this distance thus occurs transiently and may be facilitated by defined protein conformational networks involved in thermal activation [27,94]. The efficiency of active site compaction is influenced by proper steric bulk of hydrophobic residues at the active site [26,43,95,96].…”
Section: Second-order Kies Indicate Substrate Binding As Partial Ratesupporting
confidence: 79%
“…Specifically, through the application of site-specific mutagenesis, time-dependent fluorescence spectroscopic methods, and HDX-MS, two distinct long-range dynamical networks have been identified that connect solvent exposed regions of protein to the substrate binding domain (26); additionally, enthalpic barriers from kinetic measurements of Stokes shifts and T-jump FRET are seen to be identical to catalysis (15,17,27). In recent studies of a very different monomeric, single-substrate enzyme (soybean lipoxygenase), HDX-MS results link the thermal activation of a solvent-exposed loop to the positioning of the buried reactive C-H bond of substrate 15 to 30 Å away (28), once again with an enthalpic barrier for catalysis that is mirrored in Stokes shifts of a solvent-exposed chromophore (29). The goal of the present work was to extend these developed methodologies to other types of reaction, specifically the well-studied methyl transfer catalyzed by COMT (33,34,37).…”
Section: Impacts Of Y68a On the Temperature Dependence Of Catalysis Andmentioning
confidence: 83%
“…We have previously demonstrated that performing HDX as a function of temperature can uncover the regions within a protein that dominate the thermal activation of active site chemistry. In the case of C-H activating enzymes such as the thermophilic alcohol dehydrogenase (ht-ADH) (25)(26)(27) and soybean lipoxygenase (SLO) (28,29), where quantum mechanical tunneling dominates the chemical coordinate, in-depth kinetic and biophysical probes have revealed a model for catalysis in which the thermal activation barrier to reaction comes from the protein scaffold via wellresolved networks that connect solvent-exposed surfaces to the enzyme active site (26)(27)(28)(29)(30)(31).…”
mentioning
confidence: 99%
“…Redox reactions and mitochondria produce weak UV photons that might excite Tryptophan and Tyrosine amino acids 21 , 22 in proteins, as well nucleotides of DNA and RNA. Also an anisotropic momentum transfer operated by water molecules or ions could make the job 23 . In either cases of metabolically generated photons or of ion collisions (phosphate stemming from ATP hydrolysis or other) we can assume that the external energy input for a biomolecule occurs through the generation of “hot points”, as in the case of light activated fluorophores, and mediated by either radiative or collisional electronic excitation.…”
Section: Discussionmentioning
confidence: 99%